Hacking for dummies - Beaver, Kevin (Wiley Pub., 2010)
"This beginner guide to hacking examines some of the best security measures that exist and has been updated to cover the latest hacks for Windows 7 and the newest version of Linux. Offering increased coverage of Web application hacks, database hacks, VoIP hacks, and mobile computing hacks, this guide addresses a wide range of vulnerabilities and how to identify and prevent them. Plus, you'll examine why ethical hacking is oftentimes the only way to find security flaws, which can then prevent any future malicious attacks. Hacking For Dummies, 3rd Edition shows you how to put all the necessary security measures in place so that you avoid becoming a victim of malicious hacking"--Resource description page
Includes bibliographical references and index. - Print version record
Keywords: Computer security; Computer networks -- Security measures; Hackers; Computer Security; Sécurité informatique; Réseaux d'ordinateurs; Sécurité; Mesures; Pirates informatiques; COMPUTERS; Internet; Security; COMPUTERS; Networking; Security; COMPUTERS; Security; General; Computer networks; Security measures